Teacher Knowledge of Oral Language and Literacy Constructs: Results of a Randomized Controlled Trial Evaluating the Effectiveness of a Professional Learning Intervention. (2nd January 2021) - Goldfeld, Sharon; Snow, Pamela; Eadie, Patricia; Munro, John; Gold, Lisa; Orsini, Francesca; Connell, Judy; Stark, Hannah; Watts, Amy; Shingles, Beth
ABSTRACT: Teacher knowledge is a critical factor in student success. In the Classroom Promotion of Oral Language cluster randomized controlled trial, we aimed to determine whether a teacher professional learning intervention focused on promoting oral language led to improved teacher knowledge. We report a study of the impact of professional learning on teacher knowledge of oral language and literacy constructs. The intervention comprised four days of face-to-face professional learning for early years' teachers, and ongoing school implementation support. Teacher knowledge was measured through a survey at baseline, 12 months and 24 months (n = 40 intervention, n = 38 control). Teachers in the intervention arm made more correct responses on survey items than teachers in the control arm, at both time points. The professional learning intervention improved teacher knowledge in the short-to-medium term.